The Development of QM-Fudan Higher Education Online Course Quality Standards: Some Results and Analysis. Issue 3 (3rd July 2017) - Ding, Yan; Gao, Yaping; Lu, Fang
ABSTRACT: This paper aims to examine whether and how the US-based Quality Matters (QM) Higher Education Rubric-Design Standards for Online and Blended Courses apply to the Chinese higher education environment. Suitability and matchability of QM Standards are respectively examined through a questionnaire and course reviews at Fudan University, a leading research institution in China, with which Quality MattersTM has an exclusive five-year cooperation agreement to develop an adapted Chinese rubric based on the QM Standards. Cross-referencing the dimensions of suitability and matchability, QM Standards are divided into four categories, namely, Perfect, Challenging, Potential and Chicken-ribs standards. This classification helps to identify what standards are ready for adoption and what standards need to be adapted. It is found that most QM Standards are thought to be suitable for the Chinese higher education environment, but China has a long way to go to meet these standards. On the whole, QM Standards on course format, function, and basic quality elements are relatively easy for Chinese online courses to meet while the advanced standards on course quality, particularly those relating to learning outcomes, assessment and evaluation, interaction and other aspects of course design remain challenging at the present time. The research findings not only show areas of course design in China that need improvement, but also lay a solid foundation for the development of QM-Fudan Standards, which will be supplemented and improved by future practice and research based on the actual condition and progress of online education in China.